The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1108/ara-02-2014-0027
|View full text |Cite
|
Sign up to set email alerts
|

Political competition and environmental reporting

Abstract: Purpose – The purpose of this paper is to investigate the relationship between “political competition” and “environmental reporting” by New Zealand local governments. Design/methodology/approach – The research method includes a longitudinal analysis of environmental reporting by New Zealand local governments in their annual reports for the financial years 2005-2006 to 2009-2010. “Content analysis” was used to attach scores to the extent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Meanwhile, Mir et al (2015) reported a positive effect between "political competition" and "environmental reporting." The number of local governments in New Zealand that reported voluntary environmental information increased throughout the financial years of 2006-2007 and 2007-2008, compared to the previous year of 2005-2006. Nevertheless, there was a decline in the number of local authorities providing this data following the 2007-2008 fiscal year.…”
Section: Green Accounting In the Public Sectormentioning
confidence: 99%
“…Meanwhile, Mir et al (2015) reported a positive effect between "political competition" and "environmental reporting." The number of local governments in New Zealand that reported voluntary environmental information increased throughout the financial years of 2006-2007 and 2007-2008, compared to the previous year of 2005-2006. Nevertheless, there was a decline in the number of local authorities providing this data following the 2007-2008 fiscal year.…”
Section: Green Accounting In the Public Sectormentioning
confidence: 99%
“…Voters as principals hold an interest in their self-economic welfare, so they have incentives to monitor agents' actions because the wealth of voters depends on the actions of agents (Zimmerman, 1977). García-Sánchez et al (2013) and Mir et al (2015) studied the determinants of voluntary reporting by local government using the agency theory approach. Their study revealed that local governments with high political competition disclosed more information about social and environmental information voluntarily.…”
Section: Literature Review and Hypothesis Development Agency Theory A...mentioning
confidence: 99%
“…Nevertheless, research on the determinants of disclosure in local government mainly focuses on political competition and local government characteristics (Bolívar et al, 2013;García-Sánchez et al, 2013;Laswad et al, 2005;Mir et al, 2015;Prado-Lorenzo and Garcia-Sanchez, 2010). García & García-García (2010) and Mir et al (2015) found that political competition leads to greater disclosure in local government to satisfy principals. Higher political competition encourages mayors in local government to report more information since their re-election victory depends on voters' decisions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Qiu and Yang [18] believed that the government plays an important coordinating role in environmental protection, and the implementation of the emission permit trading system is conducive for compensating the environmental protection costs of upstream companies and can promote the realization of Pareto optimal. Mir et al [19] studied the relationship between government competition and environmental information disclosure in New Zealand, and the results showed that intensified political competition is conducive for increasing environmental information disclosure. rough the analysis of data from 29 provinces and cities in China, Li and He [20] studied the interaction between regional competition, environmental taxes, and green technology innovation.…”
Section: E Government's Role In the Environmentmentioning
confidence: 99%